2022
DOI: 10.3390/jpm12020260
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the Elastic Component and Venous Wall Arterialization in Patients with Venous Reflux

Abstract: Chronic venous disease (CVeD) is defined as a set of disorders affecting the venous system mainly manifested in the form of varicose veins. CVeD is characterized by a sustained venous hypertension, leading to a plethora of functional and structural changes in the vein that may cause valve incompetence and pathologic reflux. In turn, venous reflux aggravates the venous hypertension and enhances the progression of CVeD into the most advanced stages. Previous studies have proposed that there are several alteratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The extreme signs of the disease include inflammation, skin changes, and then VLU, 1 which are usually related to the poor well‐being of patients. It was already shown that in young patients with venous reflux, the venous system appears to present an enhanced dynamism and arterialization of the venous wall, which may be a reason for the premature aging and a pathological environment of the tissue 11 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The extreme signs of the disease include inflammation, skin changes, and then VLU, 1 which are usually related to the poor well‐being of patients. It was already shown that in young patients with venous reflux, the venous system appears to present an enhanced dynamism and arterialization of the venous wall, which may be a reason for the premature aging and a pathological environment of the tissue 11 …”
Section: Introductionmentioning
confidence: 99%
“…It was already shown that in young patients with venous reflux, the venous system appears to present an enhanced dynamism and arterialization of the venous wall, which may be a reason for the premature aging and a pathological environment of the tissue. 11 Aside from its substantial predominance, CVI has a considerable negative influence on living standards. CVI affects the functional capacity of patients, even in those with a milder form of the disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathophysiologically, CVeD is characterized by an ambulatory venous hypertension, which affects the venous valves, compromising the venous return, frequently in the lower limbs [ 11 , 12 ]. The persistent hypertension is a major source of local and systemic inflammation, leading to an increase in oxidative stress, endothelial dysfunction, chronic hypoxia, matrix remodeling and so on [ 13 , 14 , 15 , 16 ]. Eventually, in advanced stages of the disease, skin changes such as pigmentation, lipodermatosclerosis and ulcerations can be observed [ 17 ].…”
Section: Introductionmentioning
confidence: 99%